Engaging through Co-design in the science museum - Torhild Skatun (Museum & Society)
A co-design process that holds the potential to facilitate museum engagement will be the topic of this article. I report from a series of workshops called ‘Science, Identity and Belonging’, during which a group of museum professionals worked together with young people to co-design a museum activity. The focal point will be the way engagement materializes in the meeting between museum and youths in a creative development process of a digital installation parallel to the making of a temporary exhibition.